An Efficient S.brunken Estimators For The Mean Of Normal Population With Kuown Variance - AI- Goburi, A. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This article co;nsiders a shrunken estimator Â·Of Al-HermyariÂ· and AI Gobuii (.1) to estimate the mean (8) of a normal clistributicm N (8 cr4) with known variance (cr+), when <:I guess value (So) av11il ble about the mean (B) asÂ· an initial estrmate. This estimator is shown to be more efficient tl1an the class-ical estimators especially when 8 is close to 8â€¢. General expressions .for bias and MSE -of considered estitnator are gi ’en, witeh some examples. Nut.nerical cresdlts, comparisons and conclusions ate reported.